Early Tracheostomy in Patients With Traumatic Cervical Spinal Cord Injury Appears Safe and May Improve Outcomes. Issue 16 (August 2018) - Flanagan, Christopher D.; Childs, Benjamin R.; Moore, Timothy A.; Vallier, Heather A.
Abstract : Study Design: Retrospective case series. Objective: To characterize outcomes associated with tracheostomy timing following traumatic cervical spinal cord injury (CSCI). Summary of Background Data: The morbidity associated with cervical spine trauma is substantially increased in the setting of concomitant CSCI. Despite recent evidence, it remains uncertain if early tracheostomy following traumatic CSCI can improve outcomes. Methods: From January 1, 2007 to December 31, 2015, retrospective chart review identified 70 patients who presented to a single Level 1 trauma center with traumatic CSCI and received tracheostomy for management of respiratory compromise. Patients were subdivided into two groups based on time from initial intubation to tracheostomy procedure: early (tracheostomy ⩽7 d from initial intubation) and late (>7 d from initial intubation). Results: This series included 75.7% males and 24.3% females with mean age 50.5 years. A chest injury was present in 31.4% of patients. AIS A was the most common AIS score (41.4%), and 70.1% of patients had an injury level at C4 or above. Early tracheostomy was performed in 52.4% of patients. Factors most predictive of early tracheostomy were more severe AIS score (odds ratio [OR] = 1.72) and higher neurological level of injury (OR = 1.91) ( P < 0.001, pseudo- R 2 = 0.241). Controlling for AIS and neurological level of injury, early tracheostomy was associated with fewer ventilator days (23.9 vs. 36.9, P = 0.0268), fewer days to decannulation (53.0 vs. 74.3, P = 0.0075), and shorter intensive care unit (ICU) stays (20.7 vs. 26.0, P = 0.0217). Rates of pneumonia, surgical site infection, in-hospital mortality, 90-day mortality, and 90-day readmission rates were not different between groups. Conclusion: Tracheostomy within 7 days of intubation may improve respiratory outcomes in patients with traumatic CSCI, regardless of level or severity of injury, without increasing complication rates. Level of Evidence: 4